Innovative Managed Care May Be Related to Improved Prognosis for Acute Myocardial Infarction Survivors. Issue 8 (18th August 2021) - Jankowski, Piotr; Topór-Mądry, Roman; Gąsior, Mariusz; Cegłowska, Urszula; Eysymontt, Zbigniew; Gierlotka, Marek; Wita, Krystian; Legutko, Jacek; Dudek, Dariusz; Sierpiński, Radosław; Pinkas, Jarosław; Kaźmierczak, Jarosław; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Mortality following discharge in myocardial infarction survivors remains high. Therefore, we compared outcomes in myocardial infarction survivors participating and not participating in a novel, nationwide managed care program for myocardial infarction survivors in Poland. Methods: We used public databases. We included all patients hospitalized due to acute myocardial infarction in Poland between October 1, 2017 and December 31, 2018. We excluded from the analysis all patients aged <18 years as well as those who died during hospitalization or within 10 days following discharge from hospital. All patients were prospectively followed. The primary end point was defined as death from any cause. Results: The mean follow-up was 324.8±140.5 days (78 034.1 patient-years; 340.0±131.7 days in those who did not die during the observation). Participation in the managed care program was related to higher odds ratio of participating in cardiac rehabilitation (4.67 [95% CI, 4.44–4.88]), consultation with a cardiologist (7.32 [6.83–7.84]), implantable cardioverter-defibrillator (1.40 [1.22–1.61]), and cardiac resynchronization therapy with cardioverter-defibrillator implantation (1.57 [1.22–2.03]) but lower odds of emergency (0.88 [0.79–0.98]) and nonemergency percutaneous coronary intervention (0.88 [0.83–0.93]) and coronary artery bypass grafting (0.82 [0.71–0.94]) during the follow-up. One-year all-cause mortality was 4.4% among the program participants and 6.0% in matched nonparticipants. The end point consisting of all-cause death, myocardial infarction, or stroke occurred in 10.6% and 12.0% ( P <0.01) of participants and nonparticipants respectively, whereas all-cause death or hospitalization for cardiovascular reasons in 42.2% and 47.9% ( P <0.001) among participants and nonparticipants, respectively. The difference in outcomes between patients participating and not participating in the managed care program could be explained by improved access to cardiac rehabilitation, cardiac care, and cardiac procedures. Conclusions: Managed care following myocardial infarction may be related to improved prognosis as it may facilitate access to cardiac rehabilitation and may provide a higher standard of outpatient cardiac care.